Management Consulting: Towards an Integrative Framework of Knowledge, Identity, and Power. (28th November 2019) - Mosonyi, Szilvia; Empson, Laura; Gond, Jean‐Pascal
Abstract: This paper reviews the past 28 years of scholarship on management consulting to synthesize the field and establish more broadly its contribution to management research. Through a systematic review of 219 articles, we identify three core conceptual themes – knowledge, identity, and power – that have dominated the literature to date. Through a thematic inductive analysis of a subsection of articles, we then investigate how these themes have been defined, used, and linked. This allows us to uncover and problematize the relationships between these themes. In making explicit underlying theoretical assumptions and relationships between knowledge, identity, and power, we induce a unique framework that can guide and support future studies, instigate metaparadigmatic dialogue, and thus help consolidate the field.